Indicadores de trata de personas en mujeres que ejercen la prostitución en locales de alterne de la Comunidad de Madrid (España) - Silva, Eva A.; Manzanero, Antonio L.; Bengoa, Garazi; Contreras, María José (Acción Psicológica, 2018)
Resumen El objetivo general del presente trabajo fue la realización de un estudio sobre la situación de las mujeres que ejercen la prostitución en el entorno de la Comunidad de Madrid (España) en el contexto específico de los locales de alterne y la posibilidad de que estén siendo víctimas de redes de trata de personas.. Se analizaron 180 entrevistas a mujeres que ejercían la prostitución en locales de la periferia de Madrid (España). Los resultados analizados mostraron que la mujer que se dedica a la prostitución tiene una media de 32,57 años; proceden de Latinoamérica, Europa y en menor número de África; en su mayoría han realizado algún tipo de estudio. Un 80,5% dijo tener familia, indicando que aproximadamente un 68% tenían entre 1 y 4 hijos. Así mismo, se procedió al análisis de las preguntas respondidas o evitadas por estas mujeres, pudiéndose concluir que éstas omiten información relevante sobre muchas de las preguntas realizadas sobre los indicadores de trata y explotación, lo que permite sospechar que pudieran estar instruidas para no facilitar información sensible, bloqueando así las posibilidades de ayuda. Todo ello, permite alertar sobre la situación de vulnerabilidad de las mujeres entrevistadas. Abstract The objective of the present study was to carry out a study on the situation of women practicing prostitution in the community of Madrid (Spain), within the specific context of strip clubs and the possibility of them being victims of human trafficking networks. A total of 180 interviews were conducted on women practicing prostitution in strip clubs across the periphery of Madrid. The results analyzed show that, on average, women who engage in prostitution are 32.57 years of age; from Latin America, Europe or, from Africa (less frequently); and have generally undertaken some type of study/course. Around 80.5% of these women reported having a family, indicating that approximately 68% had between 1 and 4 children. Moreover, the present study analyzed the questions answered or avoided by these women, concluding that most of them omit relevant information regarding questions about trafficking and exploitation indicators. This finding leads to the suspicion that these women could be instructed / taught not to facilitate sensitive information, thus blocking the possibilities of help. A relationship of dependence between the testimony’s credibility estimation and the possibility of being a victim of human trafficking was found. A 94.4% of women whose testimony was believed to be credible were not considered to be victims of human trafficking; 72.8% of those estimated as non-credible were considered to be victims of human trafficking. The possibility of the interviewees being victims of human trafficking, according to interviewers, depended on their social isolation, fear or concern shown throughout the interview, their lack of collaboration, and their avoidance of certain relevant issues or being susceptible. Overall, the present study alerts about the situation of vulnerability of the interviewed women.